Auto Boat Pembersih Sampah Sungai - Rizka Fadhila Dhuha (Fakultas Teknik Elektro - Universitas Sultan Ageng Tirtayasa, 2018)
Garbage is the causes of largest the contamination of water in the river especially garbage from houses, like trash plastic cause to flow river clogged. To maintaining the cleanliness of the river from trash to the survey specifically in the garbage in the the surface of the water they are also required to an apparatus that can used with easy . In research this has been designed a piece of equipment a cleaning the garbage of a river made resembling a boat. System designed consisting of mikrokontroler, motor dc, propeller, module esp, and motor servo. This river garbage cleaning equipment operated by using a wireless control that can be connected through smartphone using an application called wifi rc esp8266 car and motorcycle dc at the center of the roumanians servo motor boat as motors jarring garbage. The results of testing showed boat can be in operate through a smartphone with a radius of 10 meters , if more than 10 meters specification will disconnect because of a module node mcu only 10 meters .